2010
DOI: 10.1160/th09-09-0650
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of prothrombinase by activated protein C during prothrombin activation

Abstract: SUMMARY Activated protein C (aPC) proteolytically inactivates factor Va (FVa) and thereby down regulates prothrombinase. Although FVa inactivation by aPC has been studied extensively, the inactivation of prothrombinase during prothrombin activation has not. Therefore, prothrombin activation initiated both without and with aPC (5.0, 7.5 or 10.0nM) was monitored over time by fluorescence. The experiments were performed with 0.075nM FVa and 1.0nM FXa, and with these concentrations reversed. The time courses of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…While the difference in initial rates of prothrombin activation by prothrombinase between wild-type and PT6 were minimal (Table 1), there was a large difference in total thrombin generation at completion (Figs 4 and 5), comparable with the effect observed in the peptide inhibition studies. A similar observation has been reported previously by our group 42 , whereby decreases in total thrombin generation are not accompanied by proportional decreases in the initial rates of prothrombin activation. Effects on the initial rates of thrombin generation, as well as total thrombin generation were accentuated only when prothrombin was activated in the presence of FVa, indicating FVa dependence of inhibition.…”
Section: Discussionsupporting
confidence: 90%
“…While the difference in initial rates of prothrombin activation by prothrombinase between wild-type and PT6 were minimal (Table 1), there was a large difference in total thrombin generation at completion (Figs 4 and 5), comparable with the effect observed in the peptide inhibition studies. A similar observation has been reported previously by our group 42 , whereby decreases in total thrombin generation are not accompanied by proportional decreases in the initial rates of prothrombin activation. Effects on the initial rates of thrombin generation, as well as total thrombin generation were accentuated only when prothrombin was activated in the presence of FVa, indicating FVa dependence of inhibition.…”
Section: Discussionsupporting
confidence: 90%
“…It has been widely reported that FXa shields FVa from degradation by APC through its reversible association in the prothrombinase (FXaFVa) complex [ 34 - 38 , 44 ]. The mechanistic basis of this protection has been conceptualized as a mutually exclusive competition for association with membrane bound FVa, so that when FVa is associated with FXa it is not a substrate for APC [ 35 ], at least at the Arg 506 site [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…We did so in stepwise fashion, analyzing the time course of FVa inactivation in empirical reaction systems with increasing number of interacting components and generating corresponding model constructs of each reaction system. Reaction mechanisms, rate constants and equilibrium constants informing these model constructs were initially derived from various research groups reporting on APC inactivation of FVa in isolation [ 22 , 31 - 33 ], in the presence of FXa [ 14 , 34 - 38 ], and in the presence of prothrombin [ 39 , 40 , 58 ]. Model predictions were assessed against empirical time course data measuring the appearance and disappearance of multiple FVa degradation intermediates as well as prothrombinase activity changes, with experiments done multiple times, with plasma proteins derived from multiple preparations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation